Evaluation of dry matter, starch content and Î²-carotene in F1 progenies of a cross between white fleshed and orange fleshed sweet potato - Nair, Aswathy GH; P, Vidya; J, Sreekumar; C, Mohan (JOURNAL OF ROOT CROPS, 2016)
Sweet potato (Ipomoea batatas (L.) Lam.) is one of the valuable crops producing the highest root dry matter content for human consumption. Sweet potato breeding is very challenging due to its genetic complexity. The tuber flesh colour variation ranges from white, cream, yellow, orange and purple. High dry matter content, carotene and anthocyanins are the main tuber characters preferred by consumers and processors. In this study, a population consisting 200 F1 progenies from a cross of S-1 (white fleshed) and ST-14 (orange fleshed) were analyzed for dry matter, starch and Î²-carotene content. The dry matter content of the progenies ranged from 18.58% (OW48) to 45.7% (OW15) and 30 per cent of the progenies showed dry matter content of 35 - 40%. The starch content accounted variations from 9.80 to 32.7 per cent and only 9 per cent showed starch content above 30%. Among the progenies, the Î²-carotene ranged from 0.02 . 11.03 mg/100g FW. The progenies OW4, OW27, OW37, OW43, OW126 and OW169 recorded the highest dry matter, Î²-carotene as well as high starch content. The tuber flesh colour variation in the progenies was done phenotypically based on 1 - 6 score. Among the progenies orange flesh colour was predominant and from the OFSP progenies, the most predominant tuber flesh colour observed was light orange (28%), orange (22%) and deep orange (4%) colour respectively.